If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -2x = 7x + 8 Reorder the terms: 26 + -2x = 8 + 7x Solving 26 + -2x = 8 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 26 + -2x + -7x = 8 + 7x + -7x Combine like terms: -2x + -7x = -9x 26 + -9x = 8 + 7x + -7x Combine like terms: 7x + -7x = 0 26 + -9x = 8 + 0 26 + -9x = 8 Add '-26' to each side of the equation. 26 + -26 + -9x = 8 + -26 Combine like terms: 26 + -26 = 0 0 + -9x = 8 + -26 -9x = 8 + -26 Combine like terms: 8 + -26 = -18 -9x = -18 Divide each side by '-9'. x = 2 Simplifying x = 2
| 15m+2n-6m+7n= | | 11z+9=-79 | | 3x^2=6x+2 | | Y=20x-2104.50 | | d+9.6=3.7 | | -(5x-8)-(4x-2)+9=-6(x-8)-(7x+2)+2 | | -78-9x=42-37x | | y-28=-49 | | 15e=-19 | | 2x^2+19=14x | | 5t-3=3t+3 | | 34+n=109 | | 4x^2=39 | | 21=2a+(5+a)+a | | 8x+26=5x+14 | | -44x-2=12-9x | | 21+8x=2+7x | | 8x+17=9x+29 | | 7-2x=8-3x | | 2x+12=-54-9x | | 6x=18x+6 | | 7+2x=8+3x | | 21=2a+(5+a) | | 5x+8y+2=0 | | 21+3x=18+2x | | -6x-7=-31 | | 7x+17=9x+29 | | 18+4x=7x-5 | | X^4-2x^3-7x^2-2x-8=0 | | -19-3n=82 | | 30+2x=6x-3 | | x^2+35=-12x |